OPEN AREAS IN TRANSLATION STUDIES: ORGANIZATIONS AND BUSINESS / Áreas a serem descobertas para os estudos da tradução: organizações e business - Lambert (Katholieke Universiteit Leuven), José; Brunelière (UFSC), Jean-François (Revista de Letras, 2016)
ABSTRACT When the eminent Centre for Translation Studies (CETRA) and Target were founded at the end of the 1980s, openness to business societies and the participation of colleagues from outside Translation Studies (TS) was guaranteed, as several noteworthy publications from the 1990s and the early 2000s demonstrate. However, it now seems that discussions around business and language are continuing along other channels, and this means it may be interesting for TS to look at what is being produced by scholars from Organization Studies. There are several Brazilian initiatives that may provide a possible starting point to reflect on new academic partnerships, on the selection of new centres (e.g. in Brazil), and on themes (including organizations) for TS research. A number of illustrations from the automotive sector can provide examples of how Descriptive Translation Studies (DTS) methods, in combination with the use of the Internet, may help TS to reengage debate with other disciplines on business issues. Keywords: Descriptive Translation Studies, Globalization, Organizations. RESUMO Quando o CETRA (Centre for Translation Studies) e a revista Target foram criados no final dos anos 1980, a abertura ao business bem como a participação de colegas oriundos de outras disciplinas além dos Estudos da Tradução (ET) estavam garantidas, como demonstram algumas publicações importantes dos anos 1990 e do início dos anos 2000. Entretanto, tudo indica que as discussões relativas à relação entre business e línguas estão continuando em outros canais e que os ET teriam de observar a produção realizada por pesquisadores dos Estudos Organizacionais para encontrar novos estudos sobre esses temas. Contudo, iniciativas brasileiras podem caracterizar um ponto de partida para uma reflexão a respeito de novas parcerias acadêmicas, a seleção de novos centros (e.g. Brasil) e temas (e.g. organizações). Algumas ilustrações tiradas do setor industrial automotivo proporcionam exemplos da maneira como os Estudos Descritivos da Tradução (EDT) combinados com a utilização de Internet podem auxiliar os ET na reabertura de um debate com outras disciplinas sobre questões relacionadas ao business. Palavras-chaves: Estudos Descritivos da Tradução, Globalização, Organizações.